Kajian Teologis: Pemberitaan Firman Tuhan Berbasis Digital Era 5.0 - Rudi Ranto Siallagan; Bernatd Lubis; Monfride Renova Simanjuntak (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The preaching of the word of God does not focus on the position of pastor, or ordained minister, but rather the duties and responsibilities of every believer. The progress of the era changes all elements of society, both from the economy, social, culture, politics without exception in the ministry of preaching the word of God. The problems and challenges in the 4.0 era are still not finished, the 5.0 era is now here and has become a special problem and challenge for everyone, especially believers and this must be faced by the church. To answer this challenge, the author uses descriptive qualitative research seen from existing phenomena and interviews with church leaders. How do the church and believers respond to this and take advantage of digital opportunities in delivering the preaching of the Word of God based on digital era 5.0 without ignoring conventional methods but empowering technology and mastering technology in preaching the word of God because technology is able to break down dividing walls and connect them in a network and the preaching of the word of God continues to occur on the digital platform even though the preacher is not preaching the word of God.